Cell‐cycle regulation of NOTCH signaling during C. elegans vulval development - Stefanie Nusser‐Stein; Antje Beyer; Ivo Rimann; Magdalene Adamczyk; Nir Piterman; Alex Hajnal; Jasmin Fisher (Molecular Systems Biology)
Abstract C. elegans vulval development is one of the best‐characterized systems to study cell fate specification during organogenesis. The detailed knowledge of the signaling pathways determining vulval precursor cell (VPC) fates permitted us to create a computational model based on the antagonistic interactions between the epidermal growth factor receptor (EGFR)/RAS/MAPK and the NOTCH pathways that specify the primary and secondary fates, respectively. A key notion of our model is called bounded asynchrony, which predicts that a limited degree of asynchrony in the progression of the VPCs is necessary to break their equivalence. While searching for a molecular mechanism underlying bounded asynchrony, we discovered that the termination of NOTCH signaling is tightly linked to cell‐cycle progression. When single VPCs were arrested in the G1 phase, intracellular NOTCH failed to be degraded, resulting in a mixed primary/secondary cell fate. Moreover, the G1 cyclins CYD‐1 and CYE‐1 stabilize NOTCH, while the G2 cyclin CYB‐3 promotes NOTCH degradation. Our findings reveal a synchronization mechanism that coordinates NOTCH signaling with cell‐cycle progression and thus permits the formation of a stable cell fate pattern.